Cyclopropanation Reactions of Semi-stabilized and Non-stabilized Diazo Compounds - Allouche, Emmanuelle M. D.; Charette, André B. (Synthesis, 2019)
The cyclopropane ring is present in a large number of bioactive molecules as its incorporation often greatly alters their physiochemical properties. The synthesis of such motif is therefore of interest. Diazo compounds are versatile and powerful reagents that can be used in a broad range of reactions, including cyclopropanation processes. However, in case of unstable diazo reagents such as the donor-substituted variants, their inherent toxicity and instability have hampered their effective synthesis and utilization. Herein, we report the recent advances devoted to the safe and facile production of these potentially hazardous species and their subsequent application in cyclopropanation reactions, allowing the synthesis of more complex cyclopropylated motifs.1 Introduction2 Halomethylmetal-Mediated Cyclopropanations3 Cyclopropanations through Metallic- or Free Carbenes3.1 Transition-Metal-Catalyzed Decomposition of Diazo Compounds3.2 Metal-Free Decomposition of Diazo Compounds4 Michael Induced Ring Closure (MIRC) Reactions4.1 Sulfur Ylides4.2 1,3-Dipolar Cycloadditions5 Conclusion
Keywords: cyclopropanation; diazo compounds; carbenoids; carbenes; Michael induced ring-closure (MIRC) reactions